Cutaneous metastasis of colon adenocarcinoma: case report and review of the literature - Ioannis Nesseris; Charalambos Tsamakis; Stamatis Gregoriou; Ilias Ditsos; Eleftheria Christofidou; Dimitris Rigopoulos (Sociedade Brasileira de Dermatologia, 2013)
Skin metastases from colorectal carcinoma are rare and signal advanced disease. We present a case of an 80-year-old male with a large skin metastatic focus in the lower abdomen, a year after resection of a colonic adenocarcinoma. The patient had already finished receiving his first cycle of chemotherapy shortly before the discovery of the abdominal nodules and at the same period a chest X-ray, revealed shadows at the base of the right lung.